2016
DOI: 10.1371/journal.pntd.0004983
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Bioinformatics Analysis of Transcription Factor Genes Indicates Conservation of Key Regulatory Domains among Babesia bovis, Babesia microti, and Theileria equi

Abstract: Apicomplexa tick-borne hemoparasites, including Babesia bovis, Babesia microti, and Theileria equi are responsible for bovine and human babesiosis and equine theileriosis, respectively. These parasites of vast medical, epidemiological, and economic impact have complex life cycles in their vertebrate and tick hosts. Large gaps in knowledge concerning the mechanisms used by these parasites for gene regulation remain. Regulatory genes coding for DNA binding proteins such as members of the Api-AP2, HMG, and Myb fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…An additional key insight is that the number of ApiAP2 factors correlates with genome size across the Hemosporidia and Coccidia, and not with the complexity of their life cycles (Oberstaller et al, 2014;Reid et al, 2014;Blazejewski et al, 2015;Woo et al, 2015;Alzan et al, 2016). This is consistent with a general genome scaling law correlation even seen in bacterial systems (Van Nimwegen, 2003).…”
Section: The Cell Cycle Apiap2 Connectionsupporting
confidence: 62%
“…An additional key insight is that the number of ApiAP2 factors correlates with genome size across the Hemosporidia and Coccidia, and not with the complexity of their life cycles (Oberstaller et al, 2014;Reid et al, 2014;Blazejewski et al, 2015;Woo et al, 2015;Alzan et al, 2016). This is consistent with a general genome scaling law correlation even seen in bacterial systems (Van Nimwegen, 2003).…”
Section: The Cell Cycle Apiap2 Connectionsupporting
confidence: 62%
“…Moreover, the cell cycle process was the most significantly enriched GO term of the biological processes category, as indicated by the DE-mRNAs in the HT, LO and HL groups. In the current study, topoisomerase II-associated protein (PAT1), a gene that accurately facilitates chromosome separation during cell division (Alzan et al, 2016), showed significantly decreased expression under the three different environmental stresses relative its expression under control conditions (Fig. 2).…”
Section: Discussionmentioning
confidence: 62%
“…There are diverse mechanisms through which the host defends against this parasitic attack, however, there have been very limited efforts made to understand the process of invasion of the erythrocytes by B. microti parasites and the many molecules associated with this process (Montero et al, 2009 ; Sun et al, 2011 ). The molecules that are involved in this process of invasion are likely to be important virulence factors (Alzan et al, 2016 ) that can be explored as potential candidates for vaccine development or to develop novel therapies, with the ultimate goal of preventing babesiosis and eradicating Babesia parasites. Our research presented here led to several interesting findings, some of which may have direct therapeutic application.…”
Section: Discussionmentioning
confidence: 99%